Fresh lemon juice supplementation for the prevention of recurrent stones in calcium oxalate nephrolithiasis: A pragmatic, prospective, randomised, open, blinded endpoint (PROBE) trial. (January 2022) - Ruggenenti, Piero; Caruso, Maria Rosa; Cortinovis, Monica; Perna, Annalisa; Peracchi, Tobia; Giuliano, Giovanni Antonio; Rota, Stefano; Brambilla, Paolo; Invernici, Giuliana; Villa, Davide; Diadei, Olimpia; Trillini, Matias; et al.
Summary: Background: Standard diet with normal calcium and reduced animal proteins and salt content reduces stone recurrence in calcium oxalate nephrolithiasis. Whether lemon juice supplementation further reduces recurrence rate is unknown. Methods: In this single-centre, prospective, randomised, open, blinded endpoint trial (Clinical Trials gov NCT01217372) we evaluated the effects of fresh lemon juice supplementation (60 mL twice daily) versus no supplementation, on time to stone recurrence in 203 patients with recurrent idiopathic calcium oxalate nephrolithiasis who were all prescribed a standard diet. Patients were included between July 2009 and March 2017 at the Nephrology Unit of the Papa Giovanni XXIII hospital in Bergamo, Italy. Time to stone recurrence at 2 years of follow-up was the primary outcome. Analyses were by intention-to-treat. Findings: During two years of follow-up 21 of 100 patients randomised to lemon juice supplementation and 32 of 103 controls randomised to no supplementation had stone recurrence [HR (95% CI): 0·62 (0·35–1·07), p = 0·089]. Patient adherence to lemon juice supplementation, however, progressively decreased from 68% at one-year to 48% at two-year follow-up. At explorative analyses restricted at one-year follow-up, ten patients with supplementation versus 22 controls had stone recurrence [0·43 (0·20–0·89), p = 0·028]. After adjustment by age, sex and normo or hypocitraturia, the HR (95%) was still significant [0·45 (0·20–0·93), p = 0·036]. At six months, 24 hour urinary sodium excretion decreased by 8·60±65·68 mEq/24 h in patients receiving lemon juice supplementation and increased by 3·88±64·78 mEq/24 h in controls. Changes significantly differed between groups ( p = 0·031). This difference was subsequently lost. Treatment was safe. In patients with lemon juice supplementation gastrointestinal disorders were more frequent ( p <0·001). Renal and urinary tract disorders were similar between groups ( p = 0·103). Interpretation: Explorative analyses suggest that f resh lemon juice supplementation to standard diet might prevent stone recurrence in patients with calcium-oxalate nephrolithiasis. However, treatment effect was likely reduced by progressively declining adherence to lemon juice supplementation. Funding: This study received no funding.